Noninvasive Measurement of Three-Phase Currents - Prasad Shrawane; Tarlochan S. Sidhu (IEEE Open Journal of Industry Applications, 2024)
This article presents a noninvasive method of measuring three-phase currents using magnetic sensors that can be used for continuous monitoring, automation, and protection of power grids. The nonintrusive nature of these sensors gives operational and economic benefits in installing them at the existing distributed generation sites and power substations. These sensors are linear in operation, free of saturation, and need minimum duration or no outage for installation as compared to the conventional current transformers. This article describes magnetic field simulation, calibration, and experimental validation of magnetic sensors for accurate measurement of three-phase currents. Laboratory experiment results of three-phase low current measurements for two types of overhead structures: triangular and horizontal are rendered as a validation of the proposition. The performance verification of these sensors is further achieved by conducting field experiments for measuring currents up to 1500 A. The sensors yield promising results with a maximum error of 1.15% in the estimation of three-phase currents. The magnetic sensors showed satisfactory performance in accurately reproducing current waveforms consisting of fundamental frequency and harmonics that are typically present in modern power grids.